Effect of Tm of blend components on the isothermal melt-crystallization process of PHB/PLLA blends investigated using spectroscopic imaging and DSC. (6th May 2022) - Lu, Huiqiang; Sato, Harumi; Kazarian, Sergei G.
Abstract: The understanding of morphology and crystallization in biopolymer blends offers the ability to tune these properties for specific uses. In this study, the isothermal melt-crystallization process of poly (3-hydroxybutyrate) (PHB)/poly (l -lactic acid) (PLLA) blends with different weight loadings and molecular weights was investigated using in-situ attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopic imaging and differential scanning calorimetry (DSC). When the isothermal crystallization temperature is constant, increasing the fraction of blend component with a lower Tm results in the decreasing Tm of both blend components, which is indicated in DSC thermograms. The reduced Tm delays the crystallization of both blend components and then the restrained crystallization leads to a greater extent of phase separation, which is shown in ATR-FTIR spectroscopic images. Likewise, at a constant isothermal crystallization temperature, with the decreasing molecular weights of blend components, the miscibility of polymer blend should be enhanced because of the shift of the phase boundary in phase diagram to lower temperatures. However, the decreasing overall crystallization rate and the delay of crystallization indicated in the integrated absorbance profiles and the decreasing Tm indicated in the DSC thermograms can be used to explain the greater extent of phase separation in the PHB/PLLA blend shown in the spectroscopic images. A phase diagram was prepared to show the effect of polymer molecular weight on the miscibility of PHB/PLLA blends. Thus, increasing the fraction of the blend component with a higher Tm, choosing polymers with a higher molecular weight and decreasing the isothermal crystallization temperature have been demonstrated to be effective methods to promote the miscibility of upper critical solution temperature (UCST) crystallizable polymer blends. Moreover, it was concluded that in-situ ATR-FTIR spectroscopic imaging can be combined with integrated absorbance profiles and DSC thermograms to deepen the understanding of multicomponent polymer systems. Graphical abstract: Image 1 Highlights: A phase diagram was prepared to show the effect of Mw on the miscibility of PHB/PLLA blends. Effective methods are found to promote the miscibility of UCST polymer blends during isothermal crystallization process. Spectroscopic imaging can be combined with DSC thermograms to deepen the understanding of multicomponent polymer systems.